2019
DOI: 10.1371/journal.pbio.3000444
|View full text |Cite
|
Sign up to set email alerts
|

The developmental Wnt signaling pathway effector β-catenin/TCF mediates hepatic functions of the sex hormone estradiol in regulating lipid metabolism

Abstract: The bipartite transcription factor β-catenin (β-cat)/T cell factor (TCF), formed by free β-cat and a given TCF family member, serves as the effector of the developmental Wnt signaling cascade. β-cat/TCFs also serve as effectors of certain peptide hormones or growth factors during adulthood. We reported that liver-specific expression of dominant-negative Transcription factor 7 like 2 (TCF7L2DN) led to impaired glucose disposal. Here we show that, in this LTCFDN transgenic mouse model, serum and hepatic lipid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 77 publications
(125 reference statements)
1
29
0
Order By: Relevance
“…Thus, gender differences observed when expressing a dominant-negative form of TCF7L2 in hepatocytes would suggest that sex hormones regulate glucose homeostasis via repressing hepatic gluconeogenesis and regulate lipid metabolism [35]. In our study, we also found that female mice were largely unaffected by the loss of TCF7L2 function in the adipocyte, suggesting a role for female hormones to maintain glucose homeostasis.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Thus, gender differences observed when expressing a dominant-negative form of TCF7L2 in hepatocytes would suggest that sex hormones regulate glucose homeostasis via repressing hepatic gluconeogenesis and regulate lipid metabolism [35]. In our study, we also found that female mice were largely unaffected by the loss of TCF7L2 function in the adipocyte, suggesting a role for female hormones to maintain glucose homeostasis.…”
Section: Discussionsupporting
confidence: 63%
“…Wnt and TCF7L2 are regulators of lipid metabolism in hepatocytes [35], consistent with elevated plasma triglycerides associated with TCF7L2 risk variant rs7903146 [45]. Moreover, the genetic variant is localized near the regulatory region for Acyl-CoA Synthetase Long Chain 5 (ACSL5) which activates fatty acids to generate long chain fatty acyl CoA [45].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…3), consistent with a role for female hormones in the maintenance of glucose homeostasis and differences in fat distribution between male and female mice (Figs 1, 2 and 3). Correspondingly, Tian et al [25] have previously revealed crosstalk between Wnt signalling and female hormones through TCF7L2. We therefore conducted our studies on the effects of HFD exposure (see below) in male mice only.…”
Section: Discussionmentioning
confidence: 92%